Multimorbidity and frailty are associated with poorer SARS-CoV-2-related outcomes: systematic review of population-based studies - Makovski, Tatjana T; Ghattas, Jinane; Monnier-Besnard, Stéphanie; Cavillot, Lisa; Ambrožová, Monika; Vašinová, Barbora; Feteira-Santos, Rodrigo; Bezzegh, Peter; Bollmann, Felipe Ponce; Cottam, James; Haneef, Romana; Devleesschauwer, Brecht; et al. (Aging clinical and experimental research, 2024)
BACKGROUND: Estimating the risks and impacts of COVID-19 for different health groups at the population level is essential for orienting public health measures. Adopting a population-based approach, we conducted a systematic review to explore: (1) the etiological role of multimorbidity and frailty in developing SARS-CoV-2 infection and COVID-19-related short-term outcomes; and (2) the prognostic role of multimorbidity and frailty in developing short- and long-term outcomes. This review presents the state of the evidence in the early years of the pandemic. It was conducted within the European Union Horizon 2020 program (No: 101018317); Prospero registration: CRD42021249444. METHODS: PubMed, Embase, World Health Organisation COVID-19 Global literature on coronavirus disease, and PsycINFO were searched between January 2020 and 7 April 2021 for multimorbidity and 1 February 2022 for frailty. Quantitative peer-reviewed studies published in English with population-representative samples and validated multimorbidity and frailty tools were considered. RESULTS: Overall, 9,701 records were screened by title/abstract and 267 with full text. Finally, 14 studies were retained for multimorbidity (etiological role, n = 2; prognostic, n = 13) and 5 for frailty (etiological role, n = 2; prognostic, n = 4). Only short-term outcomes, mainly mortality, were identified. An elevated likelihood of poorer outcomes was associated with an increasing number of diseases, a higher Charlson Comorbidity Index, different disease combinations, and an increasing frailty level. DISCUSSION: Future studies, which include the effects of recent virus variants, repeated exposure and vaccination, will be useful for comparing the possible evolution of the associations observed in the earlier waves.
Keywords: Multiple chronic conditions; multimorbidita; prognóza; Prognosis; Multimorbidity; křehkost; COVID-19; Frailty; Aged; Humans; lidé; SARS-CoV-2; senioři